Development of a Scrub Typhus Diagnostic Platform Incorporating Cell-Surface Display Technology - Liao, Chih-Chi; Tsai, Chih-Hsuan; Lo, Huei-Ru; Lin, Pey-Ru; Lin, Chang-Chi; Chao, Yu-Chan (Frontiers in Immunology, 2021)
Scrub typhus (ST), also known as tsutsugamushi disease and caused by rickettsia Orientia tsutsugamushi, is an underestimated fatal epidemic in the Asia-Pacific region, resulting in a million human infections each year. ST is easily misdiagnosed as clinical diagnosis is based on non-specific skin eschar and flu-like symptoms. Thus, the lack of accurate, convenient, and low-cost detection methods for ST poses a global health threat. To address this problem, we adopted baculovirus surface-display technology to express three variants of TSA56, the major membrane antigen of O. tsutsugamushi, as well as the passenger domain of ScaC (ScaC-PD), on insect Sf21 cell surfaces rather than biosafety level 3 bacteria in an enzyme-linked immunosorbent assay (ELISA). Recombinant TSA56 and ScaC-PD were all properly expressed and displayed on Sf21 cells. Our cell-based ELISA comprising the four antigen-displaying cell types interacted with monoclonal antibodies as well as serum samples from ST-positive field-caught rats. This cell-based ELISA presented high accuracy (96.3%), sensitivity (98.6%), and specificity (84.6%) when tested against the ST-positive rat sera. Results of a pilot study using human sera were also highly consistent with the results of immunofluorescence analyses. By adopting this approach, we circumvented complex purification and refolding processes required to generate recombinant O. tsutsugamushi antigens and reduced the need for expensive equipment and extensively trained operators. Thus, our system has the potential to become a widely used serological platform for diagnosing ST.